Proses Pembuatan Tahu Berbahan Dasar Kacang Kedelai di Pabrik Tahu Mabar Hilir - Annisya Tanjung; Cut Nabila Afifah; Cindy Miranti; Fadlilah Al Hasanah; Sakinah Warahmah; Rabiah Afifah Daulay (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
One of the processed soybean products that is a good source of protein is tofu. for the body because of the amount of protein it contains and its high digestibility. Tofu was first made around 200 BC by one of the Chinese cooks who accidentally added nigari or salt solution to soybean juice until the clumping process occurred into a solid. Since then, tofu as a processed soybean product has been accepted as a source of health for Asians. The word tofu comes from the Chinese language, namely tao-hu or teu-hu. The word tao means soybeans, while hu means crushed or mush. In Japan, tofu is known as tohu, while in English it is called soybean curda or tofu. Soybean (Glycine Max Merr) is one of the agricultural products that is very important as a food ingredient, because the amount and quality of protein it contains is very high, which is around 40% and the composition of essential amino acids is complete and appropriate so that soy protein has a quality that is close to the quality of animal protein. Keyword: Tofu, Soybean, Protein.